Construction of the quinobenzoxazine core via gold-catalyzed dual annulation of azide-tethered alkynones with anthranils - Halnor, Swapnil V. V.; Dhote, Pawan S. S.; Ramana, Chepuri V. V. (Organic & Biomolecular Chemistry, 2023)
A new catalytic method for the construction of the quinobenzoxazine core has been developed employing the gold-catalyzed cyclization of o-azidoacetylenic ketones in the presence of anthranils. The overall process comprises of a gold-catalyzed 6-endo-dig cyclisation of o-azidoacetylenic ketone leading to a alpha-imino gold carbene and subsequent carbene transfer to anthranil leading to the 3-aryl-imino-quinoline-4-one intermediate, which undergoes 6 pi-electrocyclization and aromatization to form the central quinobenzoxazine core. This transformation provides a new approach to a diverse array of quinobenzoxazine structures, in addition to being scalable and having mild reaction conditions.